The Correlation Between Students’ Vocabulary Mastery and Their English Speaking Fluency at SMKN 1 Tenggarong - Mirza Alfarizi; Ade Ismail Ramadhan; Yeni Rahmawati (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
Speaking fluency is a fundamental skill for vocational students, particularly those in hospitality programs where effective oral communication is essential for professional interaction. Vocabulary mastery plays a crucial role in supporting students’ ability to express ideas clearly, accurately, and confidently in spoken English. This study aims to examine the correlation between students’ vocabulary mastery and English speaking fluency among eleventh-grade Hospitality students at SMKN 1 Tenggarong. A quantitative correlational design was employed, involving 36 students selected through cluster random sampling. Data were collected using two instruments: a vocabulary mastery test and a speaking fluency test assessed through a standardized scoring rubric. The speaking test evaluated students’ fluency, accuracy, and clarity of expression during oral performance. The collected data were analyzed using SPSS, including descriptive statistics and Pearson Product–Moment correlation analysis. The results revealed a very strong and statistically significant positive correlation between vocabulary mastery and speaking fluency (r = 0.972, p < 0.05). This indicates that students who possess a higher level of vocabulary knowledge tend to demonstrate greater fluency and confidence in spoken communication. The findings suggest that vocabulary development contributes substantially to students’ ability to produce smooth, meaningful, and comprehensible speech. For vocational education contexts, especially hospitality programs, strong vocabulary mastery supports students in performing workplace communication tasks such as interacting with customers, delivering information, and responding appropriately in service situations. Therefore, strengthening vocabulary instruction may enhance students’ speaking performance and better prepare them for professional communication demands. This study provides empirical evidence supporting the integration of vocabulary-focused instruction as a foundation for improving speaking fluency in vocational English learning environments.